The origins of political order : from prehuman times to the French Revolution - Fukuyama, Francis (New York : Farrar, Straus and Giroux, 2011)
Francis Fukuyama examines the paths that different societies have taken to reach their current forms of political order.
Includes bibliographical references and index.
Keywords: State, The -- History; Order -- History; Comparative government -- History; Democracy -- History